Social Realist Commitment in El tungsteno by César Vallejo. Innovation of the Mechanisms of Realistic Narrative Discourse - Mousa Abd El Azeem, Saadeya (2019)
This works examines the social realist commitment characterized in the narrative of Latin American author and Peruvian poet César Vallejo (1892). This commitment to a social realist cause is particularly seen in his novel El tungsteno (1931), a brilliant work that became one of the most outstanding novels of the first half of the twentieth-century Latin American literature. This paper first sheds light on the life and literary trajectory of Peruvian poet César Vallejo, one of the most brilliant lyricists of the twentieth century Latin America. Secondly, this work will examine the innovative narrative discourses embedded in El tungsteno. To do that, I will do an analytical study of social commitment in Vallejo’s narrative; then, I will examine the narrative discourses mechanisms used, partaking with an analytical study of the main characters and then exploring the realistic narrative context of El tungsteno, as it will be discussed in depth in this paper.